Interferometric and high time-resolution observations of naturally enhanced ion-acoustic echoes at the EISCAT Svalbard radar: Software radar and incoherent scattering - Grydeland, Tom (Universitetet i Tromsø, 2003)
We know that the visible Aurora Borealis is structured on many different scales, down to a few tens of metres. By using the EISCAT radars on Svalbard as an interferometer, we have found structures in the radio echoes from the auroral ionosphere on a scale approaching that of the visible aurora, and simultaneously with it, but at far greater ranges. In this thesis we discuss how these radar observations were made, what they imply for theoretical explanations, as well as a new framework for the design and implementation of software-defined radar and other radio science instrumentation, in particular the signal processing which made these observations possible.